Measurement of the branching fraction and CP asymmetry in B+ → J/[rho] [phi] + decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (The European physical journal. C, Particles and fields, 2019)
The branching fraction and direct CP asymmetry of the decay B+→J/ψρ+ are measured using proton-proton collision data collected with the LHCb detector at centre-of-mass energies of 7 and 8 TeV, corresponding to a total integrated luminosity of 3 fb −1. The following results are obtained: B(B+→J/ψρ+)ACP(B+→J/ψρ+)=(3.81+0.25−0.24±0.35)×10−5,=−0.045+0.056−0.057±0.008, where the first uncertainties are statistical and the second systematic. Both measurements are the most precise to date.